Programmed colorectal cancer screening decreases incidence and mortality - Roselló, Susana; Simón, Soraya; Cervantes, Andrés (Translational Gastroenterology and Hepatology, 2019)
Colorectal cancer (CRC) is the third most commonly diagnosed cancer and the second leading cause of cancer- related deaths in the world (1). Detecting and removing precancerous lesions or detecting tumors in early stages through endoscopy decreases CRC mortality (2). Randomized controlled trials (RCTs) have shown that CRC screening based on guaiac fecal occult blood testing (gFOBT) and flexible sigmoidoscopy is effective in reducing incidence and mortality rates of CRC (3).